Effect of delivery mode on Chinese women's maternal satisfaction: a moderated mediation model of support from medical staff and women's self-assessment of health - Shanshan An; Sheng Sun (Taylor & Francis Group, 2023)
Purpose In recent years, the Chinese government has implemented measures to address the rising rate of cesarean deliveries and promote vaginal births, with the aim of improving women's childbirth experience. However, non-medically necessary cesarean sections and repeated cesarean sections remain prevalent. This study seeks to explore the correlation between mode of delivery and childbirth experiences. Additionally, it examines the moderating and mediating effects of support from medical staff and women's self-assessment of health on maternal satisfaction across different delivery methods. Material and Method This cross-sectional survey was conducted with 140 Chinese mothers who were 1-10 days post-partum at three tertiary hospitals. The mothers were asked to fill out a socio-demographic data form and questionnaires related to women's maternal satisfaction, mode of delivery, self-assessed health, and perception of medical staff support while they were in the hospital after delivery. The data from the questionnaires were analyzed and compared using SPSS 24.0 and PROCESS 3.2. Results This study discovered that the mode of delivery (vaginal birth or C-section) and the perception of support from medical staff significantly influenced maternal satisfaction (β = 0.82, t = 3.42; β = 0.82, t = 10.23). Specifically, women who had a vaginal birth reported higher levels of satisfaction compared to those who had a C-section. The study also found that the perception of medical staff support played a mediating role in this relationship, indicating its influence on women's satisfaction (β = 0.78, t = 9.58; indirect effect = 0.43, Boot SE = 0.15; 95% CI= [.12-.73]). Furthermore, women's self-assessed health acted as a moderator in the relationship between the mode of delivery and medical staff support (β = −0.53, t = −2.39; indirect effect = −0.41, Boot SE = 0.19; 95% CI= [-.80-.05]). Conclusion The childbirth experience of Chinese women is greatly influenced by factors such as vaginal birth, their perception of care support from medical staff, and their self-assessment of health. This highlights the importance of healthcare professionals providing women-centered maternity services and childbirth education, which can help reduce unnecessary medical intervention and the need for tertiary obstetric care.